The Chief Secretary : Madras diaries of Alexander Falconar, 1790-1809 - Falconar, Alexander, d. 1847.; Ramaswami, N. S. (Madras : New Era, 1983)
Diaries of a British civil servant and an army officer.
"Matthew Campbell, 1823": p. 63-81.
Includes index.
Keywords: Falconar, Alexander, -- d. 1847 -- Diaries; Campbell, Matthew -- Diaries; British -- India -- Biography